Evaluation of white sweet potato tube-feeding formula in elderly diabetic patients: a randomized controlled trial - Chiao-Ming Chen; Chun-Kuang Shih; Yi-Jing Su; Kuan-Un Cheang; Shu-Fang Lo; Sing-Chung Li (Nutrition & Metabolism, 2019)
Abstract Background Elderly people with type 2 diabetes mellitus (T2DM) have an increased risk of diabetes-related microvascular and macrovascular complications, thus diabetic patients with a functioning gastrointestinal tract but without sufficient oral intake require enteral nutrition (EN) formulas to control blood glucose. White sweet potato (WSP) was a kind of sweet potato could provide a healthy carbohydrate source to EN formula. The aim of this study was to examine at risk of malnutrition T2DM patients whether a WSP-EN would attenuate glucose response and elevate nutritional index compared to a standard polymeric formulas. Methods In this randomized, parallel, placebo-controlled, pilot clinical trial to investigate the effects of EN with WSP on aged residents with T2DM in long-term care institutions. In total, 54 eligible participants were randomly assigned to either the non-WSP-EN or WSP-EN group. For 60 days, the WSP-EN group received a WSP formula through nasogastric tube via a stoma with a large-bore syringe. The participants received EN of standard polymeric formulas without WSP in the non-WSP-EN group. Results The body weight, body mass index, Mini Nutritional Assessment score, and Geriatric Nutritional Risk Index were significantly higher in the WSP-EN group (p < 0.05). Moreover, the WSP-EN intervention reduced glycated hemoglobin levels (6.73% ± 1.47% vs. 6.40% ± 1.16%), but increased transferrin (223.06 ± 38.85 vs. 245.85 ± 46.08 mg/dL), high-density lipoprotein cholesterol (42.13 ± 10.56 vs. 44.25 ± 8.43 mg/dL), and vitamin A (2.45 ± 0.77 vs 2.74 ± 0.93 μM) levels (p < 0.05). In addition, there was no important side effects including gastrointestinal intolerance with prescribed doses in our WSP-EN treated patients when compared with control ones. Conclusions The results suggest WSP incorporated into enteral formulas can improve nutrition status and glycemic control in elderly diabetic patients. Trial registration NCT02711839, registered 27 May 2015.